In-Situ Transesterification Of Micro Algae To Fatty Acid Methyl Ester (Fame) Process Control And Optimization Study Using Aspen Plus Simulation - Makin, Mohamad Zainul Wafak (Universiti Sains Malaysia, 2022)
Simulated in-situ transesterification of micro algae to fatty acid methyl ester (FAME) has been presented in this study. The simulation was carried out to study the effect of reaction time, reactor temperature, reflux ratio and the molar ratio of biomass-methanol on purity and flowrate of FAME and Glycerol in different unit operation such as Continuous Stirred Tank Reactor (CSTR), Methanol Recovery Unit (MRU) and Glycerol Recovery Column (GRC). A complete model of the esterification plant was used to simulate the result and optimization of the performance. The simulation was conducted using Aspen Plus V10. For optimal conditions at 64.8216 °C, the purity and the flowrate for FAME in CSTR are 0.007118007 and 7.8193233 kmol/hr, respectively. In addition, at optimal reflux ratio conditions of 10.9, the purity of FAME in MRU is 0.6630. Other than that, the purity of glycerol in the GRC is 0.8547 for an ideal reflux ratio of 1.8999. In addition, the Cohen-Coon tuning technique, was chosen as the controllers tuning method in this study. In overall, CSTR and Phase Separator 1 have more robust controllers since it has lower controller output percentage errors. Meanwhile, MRU and GRC controllers are more aggressive since it has high controller output percentage error.